Katsuo extract derived from dried bonito plays a role in systemic anti-inflammation and consolidation of the blood-brain barrier to regulate higher brain functions - Hokari, Yoshinori; Sekine, Aya; Kai, Yuko; Oikawa, Shino; Mano, Asuka; Ohata, Hisayuki; Sugama, Shuei; Kakinuma, Yoshihiko (Frontiers in Natural Products, 2022)
Objects: Recently, a non-neuronal cardiac cholinergic system, in which cardiomyocytes are equipped with components to synthesize acetylcholine, is considered to be important for maintaining physiological homeostasis in the heart, according to its anti-ischemia and hypoxia effects and angiogenesis-enhancing effects to salvage myocardium. Furthermore, it influences sustaining blood brain barrier functions. However, it remains to be fully elucidated whether any substance plays a role in activating the system. Methods: Using Katsuo extract derived from dried bonito, called Katsuobushi in Japanese, we performed in vitro and in vivo studies whether Katsuo extract activates the non-neuronal cardiac cholinergic system and influences the associated physiological responses, specifically focusing on anti-inflammatory property and potentiation of blood brain barrier functions. Results: Katsuo extract potently activates the non-neuronal cardiac cholinergic system and the parasympathetic nervous system. In vitro and in vivo murine models clearly showed that Katsuo extract also exerted anti-inflammatory action by suppressing cytokine production and microglial activation against pathogenic and non-pathogenic factors. Furthermore, it upregulated blood brain barrier components, such as claudin-5 and occludin, strengthened the function and prevented disruption in a brain injury model, and finally influenced murine higher brain functions by activating resiliency against depressive or anxiety-like behaviors. Conclusion: Therefore, the novel findings of this study indicate that Katsuo extract possesses characteristic anti-inflammatory and blood brain barrier consolidation effects, and the non-neuronal cardiac cholinergic system activation. The intake might be effective in influencing pathophysiology of neuroinflammation-related diseases.